Evaluation of routing policies using an interval-valued TOPSIS approach for the allocation rules. (June 2021) - Montanari, R.; Micale, R.; Bottani, E.; Volpi, A.; La Scalia, G.
Highlights: An original TOPSIS-based allocation method for low-level picking items is presented. Different routing policies are tested under TOPSIS and random allocation rules. A new KPI is introduced to test the effectiveness of TOPSIS vs. random allocation. TOPSIS allocation is effective in decreasing the travel distance of pickers. Abstract: The success of warehouse management in a supply chain widely depends on an efficient and effective retrieve of customer orders, which is known as the picking process. This paper investigates various routing policies of pickers under two different allocation methods of items in a warehouse of fixed layout, and evaluates their performance in terms of the resulting travel distance by means of a simulation approach. The allocation strategies taken into account are the random storage and a multi-criteria approach, called Interval-Value TOPSIS (IV-T), which is expressively proposed in this paper as a new way to solve the storage allocation problem of items in a warehouse. Because of the newness of the approach proposed, an ad hoc performance measure is also introduced to evaluate the effectiveness of the IV-T allocation. Results show that the usage of the IV-T approach involves interesting savings in the travel distance compared to the random allocation.